IMPACT OF WORK LIFE BALANCE ON INSTITUTIONAL COMMITMENT AMONG MATHEMATICS WOMEN TEACHERS - Jeslin, D.; Babu, G.Ramesh (International Journal of Research -GRANTHAALAYAH, 2016)
Institutional commitment is the degree to which an employee identifies with a particular institution and wishes to maintain membership in the institution. An individual who has high institutional commitment is willing to exert extra effort on behalf of the institution, and has a strong desire to remain within the institution. The high level of institutional commitment reduces absenteeism and turnover. If an employee deeply committed to their institution perform roles beyond their formal job description. These extra roles improve institutional effectiveness. Those who are deeply committed to their institution give less time to their non-work life. Those who are strongly attached and committed to their institution tended to enjoy highly successful career and non-work life as well. The reason attributed to this is the job satisfaction such employees experience and relishes help them balance their career and home life. The objective of the study was to investigate the level of institutional commitment and the impact of work life balance on institutional commitment among the mathematics women school teachers in Kanyakumari district. Out of 28 isolated bacteria, Gram positive was the most frequently isolated bacteria in hip and knee joint infection cultures, 22(78.6%) vs. 6(21.4%) (P-value < 0.05). Staphylococcus epidermidis was the most frequently isolated 13(46.5%) isolates followed by Staphylococcus aureus isolates 7(25%). On other hand Pseudomonas aeruginosa was the most frequently isolated Gram negative bacteria 3(10.7 %%) in hip and knee joint infection cultures. The most effective antibiotic on Gram-positive isolates was Vancomycin which showed 95.5%. In Gram negative bacteria the most effective antibiotics were Imipenem (100%) followed by Amikacin which showed sensitivity rate 83.33.